The Effects of Care Team Roles on Situation Awareness in the Pediatric Intensive Care Unit: A Prospective Cross‐Sectional Study. Issue 10 (19th August 2020) - Soberano, Blaise T; Brady, Patrick; Yunger, Toni; Jones, Rhonda; Stoneman, Erin; Sosa, Tina; Stalets, Erika L; Zackoff, Matthew; Chima, Ranjit; Tegtmeyer, Ken; Dewan, Maya
Abstract : Improved situation awareness (SA) decreases rates of clinical deterioration in the pediatric inpatient setting. We used a prospective, cross‐sectional, observational study to measure interprofessional care team SA for a pediatric intensive care unit (PICU) patients. The resident, bedside nurse, and respiratory therapist for each patient were surveyed regarding high clinical deterioration risk status as defined by clinical criteria identified by the PICU fellow or attending and mitigation plan. From March 2018 to July 2019, we surveyed 400 care team trios caring for 73 high‐risk patients. Nurses identified the patient's risk status correctly for 375 of 400 patients (94%), respiratory therapists, 380 (95%; P = .4), and residents, 349 (87%; P = .002). For the 73 high‐risk patients, nurses were correct 82% of the time, respiratory therapists, 85%, P = .7, and residents, 67%, P = .04. Interventions targeting resident SA are needed within the PICU, especially for high‐risk patients. Abstract :